Оптимізація файлообміну в пірінгових мережах - Петров, О. М. (ХНУРЕ, 2018)
The peer network is based on the equality of participants and is characterized by the fact that its elements can be interconnected. One area of application of data network technology is file sharing. The task of optimizing file sharing can be considered as a scheduling problem. It examines the tasks in which it is necessary to order or, in other words, to determine the sequence of performance of a set of works.
Keywords: оптимізація файлообміну; пірінгові мережі